Univerzalne vsebine Vodovnikovega pohorskega pesemskega koša na vstopu v 21. stoletje - Muršič, Rajko (Etnolog. Nova vrsta (Ljubljana), 2002)
To the anthropology of music the legacy of the Pohorje singer and poet Jurij Vodovnik continues to live on in our days. People still sing his songs, and this certainly means that they carry universal messages. Vodovnikć s activities can be compared with similar historical and local phenomena like the joculators or griots. Furthermore, the creativity of a gifted individual from the early 19th century may be compared to contemporary popular music developments from blues to chansons. The author underpins these comparisons with reflections about the common characteristics of folk music and popular music.
Keywords: Vodovnik, Jurij, 1791-1858; antropologija glasbe; popularna glasba; ljudski pevci